Estimates of smoking-attributable mortality and hospitalization in BC, 2002-2007 - Tu, A.; Buxton, J.; Stockwell, Tim (2012)
Objective: The objective of this paper was to estimate the number and rate of deaths and hospitalizations attributable to smoking in British Columbia (BC) from 2002 to 2007. Methods: Using attributable fractions adjusted to BC smoking prevalence and mortality and hospital administrative data, estimates of smoking-attributable mortality (SAM) and smoking-attributable hospitalization (SAH) were calculated by year, disease category, sex, and geographic region. Results: Among active smoking adults 15 years of age and older, there were an estimated 4,851 deaths and 25,314 hospitalizations attributed to smoking in BC in 2007. SAM and SAH rates in 2007 were estimated as 119 and 633 per 100,000, respectively. Rates increased from 2002 to 2005 but have declined in subsequent years. Lung cancer and chronic obstructive pulmonary disease were responsible for the largest proportion of SAM and SAH, respectively. There were regional differences, with the Northern Health authority having the highest rate of SAM and SAH and Vancouver Coastal Health authority having the lowest. Conclusion: Smoking still presents a substantial human and economic burden in BC. Estimates of annual SAM and SAH provide researchers with the ability to detect emerging trends, target intervention and cessation programs, and evaluate current smoking reduction programs. The methodology can be adapted to other provinces to allow for cross-province comparisons.